The Influence of Supervisor Unfair Treatment on Envy: Evidence from Indonesian Employees - Wijaya, Nikodemus Hans Setiadi; Nugraheti, Mella Kartika (Business and Entrepreneurial Review, 2025)
The influence of supervisor unfair treatment on employee envy has been relatively underexplored in the existing literature. This study addresses this gap by collecting data from 178 Indonesian employees working in various organizations and industries. The results indicate that supervisor unfair treatment significantly promotes malicious envy, while its relationship with benign envy is not significant. Additional regression analyses revealed that, among demographic variables, gender was more strongly related than age and tenure to perceived supervisor unfair treatment and both types of envy. Theoretical and practical implications of the findings are discussed, and several limitations of the study are acknowledged.